SYNTAXONOMY OF HY GROPHILOUS WOODS OF THE ALNO-QUERCION ROBORIS - BRULLO, S.; SPAMPINATO, G. (Annali di Botanica, 1999)
A syntaxonomical revision of the hygrophilous woods occurring in marshy places of the flood-plains from SE Europe is given. This vegetation is included in the Alno-Quercion roboris, alliance of the Populetalia albae, which comprises numerous associations characterized by the dominance of hard-wood trees, such as Quercus robur, Fraxinus oxycarpa, Ulmus minor, Alnus glutinosa, etc. For each association the synonyms, nomenclature type, diagnostic species, ecology, structure and chorology are given.